Watershed Approach for Wind Swept Areas in Tamilnadu Using Remote Sensing Techniques - Ghouse, S. Mohamed; Dhanasekaran, R.; Kalyani, A. (Journal of Soil and Water Conservation, 2022)
The predominant limitation to agriculture in the semi-arid climatic zone is low rainfall, combined often with with an erratic or highly seasonal distribution. The countries with land areas failing into this category include Australia, Brazil, India, Kenya, South Africa, Zimbabwe, Angola, Mozambique and South West Africa. Other African countries, in particular Ethiopia, Sudan, Chad, Niger, Mali, Algeria, Morocco and Libya, although dominated by huge areas of true arid zones also have semi-arid areas. The accelerating rate of desertification in arid and semi-arid climates’, especially in Africa, the eastern Mediterranean and southwestern Asia, is largely the result of increasing human populations and the associated agricultural land use. The major limiting factor to tree establishment and growth in the semi-arid zone is shortage of water. Shelter belts have a number of demonstrated values in agricultural land use, with the primary values associated with improving agricultural productivity and preventing or reducing land-degradation processes. Shelterbelts are commonly planted for specific protection purposes rather than as part of a general land- development program. The primal), effect of any windbreak system is the reduction in wind velocity. This reduction influences turbulent transport processes and results in a modification of the microclimate in the sheltered zone. The southern part of Peninsular India has peculiar phenomenon of wind erosion by the high velocity winds bordering the districts from West. While studying the satellite data of wind eroded areas of Uthumalai village, the new sand deposit area can be demarcated. The sand deposition intensity depending on the variation in colour from bright yellow, mixed yellow with brown, deep brown, gray, dark gray and red, can be mapped representing definite class. of land use and following observation are made, the old and new sand deposits area can be identified, Except the areas used for raising crops all other lands have sand deposits. The sand deposition depth is lowest in the east and deepest in the west near the foot hills which obstruct the wind flow and allows the sand to deposit. The flood prone area can be mapped, the satellite data can be transferred on the village map field boundaries when the continuous cultivated is more than 0.25 ha The Remote Sensing Data are useful in studying the watersheds affected by Wind Erosion and executing the Wind Erosion control measures.